2023
DOI: 10.1027/1015-5759/a000696
|View full text |Cite
|
Sign up to set email alerts
|

Civic Identity in Emerging Adulthood

Abstract: Abstract. Civic identity refers to beliefs, emotions, and experiences of individuals regarding their membership in a particular community and the perceived opportunities for their civic participation. It represents one of the most important predictors of civic engagement, yet there is little empirical evidence on its development in diverse samples. To address this gap in the literature, we constructed the Civic Identity Status Scale (CISS) to measure four identity statuses proposed by Marcia. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
(63 reference statements)
0
3
0
2
Order By: Relevance
“…The revealed higher values of the conceptuality and representation of the civic identity among other identities in middle-aged persons can be explained by the fact that older people have a broader experience of involvement in the organizational environment (hierarchical, regulatory, and legal) of the state and value-meaning exchange with fellow citizens (Lep & Zupančič, 2023) than young people who are mainly studying (which implies much narrower involvement in the organizational environment of the state) (Mitasova et al, 2021) or are just starting a career, business, and family life. This experience causes a quantitative difference in the material for comprehension and understanding (life events related to interaction with the state, the need to accept and internalize them, as well as various kinds of narratives and actualized problems) (Enright & Toledo, 2023;Martínez et al, 2023) and higher motivation (which is created by that part of the mentioned experience that contains negative experiences, causes dissatisfaction and prompts an explanation, interpretation) (Toledo & Enright, 2022;Martínez et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The revealed higher values of the conceptuality and representation of the civic identity among other identities in middle-aged persons can be explained by the fact that older people have a broader experience of involvement in the organizational environment (hierarchical, regulatory, and legal) of the state and value-meaning exchange with fellow citizens (Lep & Zupančič, 2023) than young people who are mainly studying (which implies much narrower involvement in the organizational environment of the state) (Mitasova et al, 2021) or are just starting a career, business, and family life. This experience causes a quantitative difference in the material for comprehension and understanding (life events related to interaction with the state, the need to accept and internalize them, as well as various kinds of narratives and actualized problems) (Enright & Toledo, 2023;Martínez et al, 2023) and higher motivation (which is created by that part of the mentioned experience that contains negative experiences, causes dissatisfaction and prompts an explanation, interpretation) (Toledo & Enright, 2022;Martínez et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…З'ясовані вищі значення концептуальності і репрезентованості громадянської ідентичності серед інших ідентичностей в осіб середньої дорослості можна пояснити тим, що доросліші люди мають ширший досвід залучення до організаційного середовища (ієрархічного, нормативно-правового) держави та ціннісно-смислового обміну зі співгромадянами (Lep, Zupančič, 2023), ніж молодь, яка переважно вчиться (що передбачає вужче залучення до організаційного середовища держави) (Mitasova et al, 2021) або лише розпочинає кар'єру, бізнес та сімейне життя. Цей досвід спричиняє кількісну різницю в матеріалі для усвідомлення та осмислення (життєві події, пов'язані зі взаємодією з державою, необхідність їх прийняти та інтеріоризувати, а також різного роду наративи, актуалізовані проблеми) (Enright, Toledo, 2023;Martínez et al, 2023) та вищу мотивацію (створюється тією частиною згаданого досвіду, що містить негативні переживання, спричиняє незадоволення і спонукає до пояснення, тлумачення) (Toledo, Enright, 2022;Martínez et al, 2023).…”
Section: Discussionunclassified
“…Idealtypisch für die Entwicklung ist der Aufbau von Commitment nach einem offenen Explorationsprozess in einer sogenannten erarbeiteten Identität. Es gibt querschnittliche Belege für den Zusammenhang von Interesse, Selbstwirksamkeit und einer der erarbeiteten Identität (Lep & Zupančič, 2023) Die aktive Auseinandersetzung mit politischen Themen -und die Erarbeitung einer politischen Identität -setzt ein grundlegendes Interesse an Politik voraus. Der Aufbau eines grundlegenden Interesses an politischen und sozialen Themen ist ein wichtiges Ziel von politischer Bildung und Demokratieerziehung in der Schule (van Deth & Elff, 2004).…”
Section: Introductionunclassified
“…There are some studies in the literature that handles civic identity from different perspectives. For instance, Lep and Zupančič (2023) constructed a Civic Identity Status Scale and gathered data from 493 people who are at the age of 18-29 with this scale. They found that the scale was valid and reliable and could be used in further research.…”
mentioning
confidence: 99%
“…Civic identity refers to the beliefs, emotions, and experiences of individuals regarding their membership in a particular community and the perceived opportunities for their civic participation. It represents one of the most important predictors of civic engagement, yet there is little empirical evidence of its development in diverse samples (Lep & Zupančič, 2023;Suntana & Tresnawaty, 2021). And for Kazakhstan today the main goal is to form an identity that ensures integrity within the country.…”
mentioning
confidence: 99%